The Modulation of Mucosal Antiviral Immunity by Immunobiotics: Could They Offer Any Benefit in the SARS-CoV-2 Pandemic? - Villena, Julio; Kitazawa, Haruki (Frontiers in Physiology, 2020)
Viral respiratory infections are of major importance because of their capacity to cause of a high degree of morbidity and mortality in high-risk populations, and to rapidly spread between countries. Perhaps the best example of this global threat is the infectious disease caused by the new SARS-CoV-2 virus, which has infected more than 4 million people worldwide, causing the death of 287,000 persons according to the WHO’s situation report on May 13, 2020. The availability of therapeutic tools that would be used massively to prevent or mitigate the detrimental effects of emerging respiratory viruses on human health is therefore mandatory. In this regard, research from the last decade has reported the impact of the intestinal microbiota on the respiratory immunity. It was conclusively demonstrated how the variations in the intestinal microbiota affect the responses of respiratory epithelial cells and antigen presenting cells against respiratory virus attack. Moreover, the selection of specific microbial strains (immunobiotics) with the ability to modulate immunity in distal mucosal sites made possible the generation of nutritional interventions to strengthen respiratory antiviral defenses. In this article, the most important characteristics of the limited information available regarding the immune response against SARS-CoV-2 virus are revised briefly. In addition, this review summarizes the knowledge on the cellular and molecular mechanisms involved in the improvement of respiratory antiviral defenses by beneficial immunobiotic microorganisms such as Lactobacillus rhamnosus CRL1505. The ability of beneficial microorganisms to enhance type I interferons and antiviral factors in the respiratory tract, stimulate Th1 response and antibodies production, and regulate inflammation and coagulation activation during the course of viral infections reducing tissue damage and preserving lung functionally, clearly indicate the potential of immunobiotics to favorably influence the immune response against SARS-CoV-2 virus.